Estudo da adsorção de corantes reativos pela argila chocobofe - Cavalcante, José Demétripo Nery (Universidade Federal Rural do Semi-Árido, 2019)
Since the XVIII century the world suffer for one revolution in the means of production and consumption of goods. The revolution started to develop in England with prominence in the industries of fabrics and clothes. Among the various steps of the process the dyeing is one of the most important, but since the beginning of the XIX century the dyeing occurs by the use of synthetics dyes, which are used with huge amounts of water. The process generates a problem of pollution because the wastewater remains with elevated concentrations of dyes that are discarded to the environment. The present study aims analyze the behavior of adsorption of reactive dyes by the chocobofe clay as a way to eliminate this pollutant in the wastewater from the industries.
Monografia
Keywords: Corante; Adsorção; Argila Chocobofe; ENGENHEARIAS::ENGENHARIA QUIMICA